EFFECTS OF CHRONOLOGICAL AGEING ON EPIDERMAL THICKNESS OF HUMAN SKIN IN DIFFERENT AGE GROUPS - Baqar, Ayesha; Muazam, Shazia; Rashid, Saadia; Qamar, Khadija (Pakistan Armed Forces Medical Journal, 2018)
Objective:To compare the age related changes in thickness of skin epidermis in different age groups in the Pakistani population.Study Design: Cross sectional study.Place and Duration of Study: The study was conducted at Army Medical College, Rawalpindi, for a period of five months, from Jul 2010 to Nov 2010. All protocols were approved by the Ethical committee of centre for research in experimental and applied medicine (CREAM), Army Medical College, Rawalpindi.Patients and Methods:In this study, 60 volunteers of both genders, fulfilling the inclusion criteria, were divided according to age, into three equal groups, 18-29 years, 30-49 years, and more than 50 years, Groups A, B and C respectively. All study participants gave written consent before their inclusion in the study Four-mm full-thickness punch biopsy of sun protected upper arm skin of left side was obtained from each individual after administration of local anesthetic injection. The samples were stained with Haematoxylin and Eosin for histomorphological study and comparison of epidermal thickness was done between the three groups. In each section, the epidermal thickness was measured at three points to determine maximum thickness, under 10X objective. Mean of three readings of each sample was taken. Then, mean of each group was taken and that of the three groups was compared to determine the presence or absence of epidermal atrophy.Results:There was no appreciable difference in epidermal thickness between the three groups. Mean of group A was 144.833 μm, that of group-B was 142.833 μm and the mean value of group C was 125.5 μm.Conclusion:It was concluded that, although human skin markedly deteriorates visibly with age, the epidermal thickness remains constant.